Korelasi Intensitas Puasa Senin Kamis dan Kecerdasan Emosional - Shifa Azzahra; Tsania Tazlila Wardhani; Nur Azmi; Sri Mulyani; Wismanto Wismanto (CV. Aksara Global, 2024)
This research aims to determine the relationship between the intensity of fasting Monday and Thursday with emotional intelligence in campus missionary members (HIMA). This research uses population research because the researcher uses all members of the HIMA PGMI Universita Muhammadiyah Riau (UMRI) class of 2021 and 2022, totaling 30 people. Data collection uses questionnaires and emotional intelligence scales. The data obtained was then analyzed using regression analysis. The results of the research show that there is a significant relationship between the intensity of fasting Monday and Thursday with emotional intelligence in members of the PGMI Student Association (HIMA) organization at Muhammadiyah University of Riau class of 2021 and 2022 with a value of r = 0.372; and p = 0.000.